Contribution to the knowledge of the subgenus Stigmatodipogon Ishikawa, 1965 of the genus Dipogon Fox, 1897 (Hymenoptera: Pompilidae) - Loktionov, Valery M.; Lelej, Arkady S. (Zootaxa, 2019)
Two new species, Dipogon (Stigmatodipogon) siam Loktionov & Lelej, sp. nov. and D. (S.) wasbaueri Loktionov & Lelej, sp. nov., are described and illustrated based on females from northern Thailand and Laos. The subgenus Stigmatodipogon Ishikawa of the genus Dipogon Fox is newly recorded from Thailand. An updated key to the females is provided.